STARTEGI EFEKTIF MEMBANGUN RASA TANGGUNG JAWAB MASYARAKAT DALAM PENANGGULANGAN SAMPAH DI KOTA SINTANG MELALUI AKSI KERJA NYATA MAHASISWA - Suparno, Suparno; Pertiwi, Sabna; Mustafa, Akit (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2024)
This research aims to identify and develop effective strategies in building a sense of community responsibility for waste management in Sintang City. The main focus of this research is real work actions carried out by students as agents of change in encouraging active community participation. Through surveys and qualitative analysis, this research reveals key factors that influence people's attitudes and behavior regarding waste management.The research findings highlight the importance of educational, participatory and inclusive approaches in involving students in waste management efforts. By understanding local dynamics and adapting strategies based on community needs, students' real work actions can be a significant driver for increasing community awareness and responsibility for environmental issues, especially waste management in Sintang City. The practical implications of this research can be used as a basis for designing policies and intervention programs that are more effective in increasing community participation in managing waste.Keywords: Strategy, Effectiveness, Waste Management Responsibility, Student Real Work ActionÂ